Optimal Control of Wind Energy Systems Towards a Global Approach - Munteanu, Iulian; Bratcu, Antoneta Iuliana; Cutululis, Nicolaos-Antonio; Ceanga, Emil (Advances in Industrial Control,, 2008)
Owing to the stochastic nature of their primary energy source, workable performance of wind energy conversion systems cannot be achieved without the contribution of automatic control. Optimal Control of Wind Energy Systems presents a thoroughgoing review of the main control issues in wind power generation, offering a unified picture of the issues in optimal control of wind power generation. A series of optimal control techniques are analyzed, assessed and compared, starting with the classical ones, like PI control, maximum power point strategies and gain-scheduling techniques, and continuing with some modern ones: sliding-mode techniques, feedback linearization control and robust control. Discussion is focused on a global dynamic optimization approach to wind power systems using a set of optimization criteria which comply with a comprehensive group of requirements including: energy conversion efficiency; mechanical reliability; and quality of the energy provided. The main results are presented along with illustration by case studies and MATLAB®/Simulink® simulation assessment. The corresponding programmes and block diagrams can be downloaded from the book's page at springer.com. For some of the case studies presented, real-time simulation results are also available, illustrative examples which will be useful in easing technology transfer in control engineering associated with wind power systems. Control engineers, researchers and graduate students interested in learning and applying systematic optimization procedures to wind power systems will find this a most useful guide to the field.